Interlink Platform for School, Higher and Technical Education in India: Design Platform: Analysis of academic performance and dropout rates in the Indian education system - Ghodichor, Nitesh; Chopde, Pratham; Choudhari, Mansi; Rangari, Saloni; Badge, Pratham (EAI Endorsed Transactions on Internet of Things, 2025)
This research paper aims to fill the knowledge gap in understanding the factors that contribute to academic performance and dropout rates in the Indian education system. The study proposes a “Interlinked platform for school, higher and technical education in India”, a unified digital space for students, educators, administrators and government agencies. The platform is designed to track students' academic performance across different educational levels and visualize dropout rates. The research uses a comprehensive methodology that integrates data analysis techniques and visualization frameworks and uses Python libraries such as NumPy, Pandas, Matplotlib and Scikit-Learn. Student academic outcomes are analyzed using linear regression and K-means clustering, and dropout rates are predicted using logistic regression. The aim of the research is to provide institutions with valuable insights to understand the factors that contribute to dropout rates and to develop targeted interventions to address potential triggers of dropout.
Keywords: Performance Analysis; Interlinked Platform; Dropout Prediction; Educational